2003
DOI: 10.1097/01.asn.0000069218.31647.39
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Trial on Effect of Percutaneous Transluminal Angioplasty on Functioning Arteriovenous Fistulae Survival

Abstract: Abstract. Balloon angioplasty (PTA) is an established treatment modality for stenosis in dysfunctional arteriovenous fistulae (AVF), although most studies showing efficacy have been retrospective, uncontrolled, and nonrandomized. In addition, it is unknown whether correction of stenosis not associated with significant hemodynamic, functional, and clinical abnormality may improve survival in AVF. This study was a prospective controlled open trial to evaluate whether prophylactic PTA of stenosis not associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(99 citation statements)
references
References 21 publications
12
84
1
2
Order By: Relevance
“…We found no significant relationship between the AVF location and the patency rate, consistent with other studies (8,17). In addition, no significant relationship was found between the stenosis location and the primary and secondary patency rates in many studies, including ours (17,19,22). However, Turmel-Rodrigues et al (18) reported a higher primary patency rate in cases with feeding artery stenosis.…”
Section: Discussionsupporting
confidence: 88%
“…We found no significant relationship between the AVF location and the patency rate, consistent with other studies (8,17). In addition, no significant relationship was found between the stenosis location and the primary and secondary patency rates in many studies, including ours (17,19,22). However, Turmel-Rodrigues et al (18) reported a higher primary patency rate in cases with feeding artery stenosis.…”
Section: Discussionsupporting
confidence: 88%
“…During the study period, two prospective, controlled, randomized or quasi-randomized trials that evaluated the role of PTA (30) and surveillance combined with preemptive stenosis repair (by surgery and PTA) on AVF survival (31) were completed in our institutions. Many of the data in our study were collected for these trials and now are analyzed to answer the question of whether the two stenosis treatment modalities, surgical and endovascular, had different outcome and cost.…”
Section: Methodsmentioning
confidence: 99%
“…It is currently thought that most episodes of thrombosis are due to underlying anatomic abnormalities such as access stenosis from fibromuscular and intimal hyperplasia (5,6). However, access thrombosis can occur without anatomic abnormalities (3,6,7), and it is unknown why some patients with anatomic abnormalities experience access thrombosis whereas others do not (8).…”
mentioning
confidence: 99%